Do stock splits improve liquidity? Evidence from Vienna Stock Exchange - Rudnicki, Józef (Czy podział kapitału akcyjnego przyczynia się do zwiększenia płynności? Przykład spółek notowanych na Wiedeńskiej Giełdzie Papierów Wartościowych, 2011)
The article deals with a puzzle phenomenon which are stock splits. The author examines the subsequent volume of the companies listed on the Vienna Stock Exchange after they concluded stock splits. The research aims to test the hypothesis that the liquidity of stocks that split the shares improves afterwards.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 158, s. 1050-1059
Keywords: stock split; liquidity; volume